Akuntabilitas, Partisipasi Masyarakat dan Transparansi Kebijakan Publik Sebagai Pemoderasi Hubungan Pengetahuan Dewan Tentang Anggaran Dan Pengawasan Keuangan Daerah - Isma Coryanata (Journal of Accounting and Investment, 2011)
This study examined influence of accountability, public participation, and public policy transparency on the relationship between budgeting knowledge and budgeting control. The study sample was from kota Bengkulu. Thirty legislative participated in this study. Hypothesis are tasted empirically used regression.The result of study indicated that, first, budgeting knowledge are statically significant, positive coefficient indicated that high budgeting knowledge so high budgeting control. Second, all moderating variables were accountability, public participation, and public policy transparency had the relationship between budgeting knowledge and budgeting control. Therefore this study sported anothetr studies before.